The Impact of Macroeconomic Factors over the Performance of the Banking Sector in Republic of North Macedonia - Imeri, Berkan; Sucubasi, Bilal; Merdzan, Gunter (Dilkur Akademi, 2020)
Monitoring and assessment of the performance of banks and the banking sector as a whole, presents a serious challenge, especially in the environment in which they operate today. The needs and demands of the clients are constantly increasing and changing, as well as the regulatory requirements, which influence the banking operation process, their efficiency, and effectiveness. This paper examines the importance and effects of the macroeconomic factors over the performance of the banking sector in the Republic of North Macedonia, considering the trend in the banking industry. Thus, the logic behind this research is to determine whether and in which direction are aimed effects of some selected macroeconomic variables. The relation between the profitability of the banking sector and some macroeconomic variables has been analyzed by employing ordinary least squares method, to perceive the results of the sector and to identify trends in the key indicators and the factors affecting the performance. The study is based on secondary quarterly data on the performance of the banking sector and some selected macroeconomic variables published by the NBRNM, as well as data from the banks’ financial statements for the period between 2010-2019. The general conclusion from this analysis is that the unemployment rate and average net salary growth both significantly affect the profitability of the banking sector in the Republic of North Macedonia, but GDP growth and the National Bank policy rate both are statistically insignificant in the model.
Keywords: ROAA; banking sector; macroeconomic factors; ordinary least squares method